PENGARUH LITERASI KEUANGAN DAN FINTECH MELALUI INKLUSI KEUANGAN TERHADAP PERKEMBANGAN UMKM SEKTOR PANGAN DI KOTA BENGKULU - Fella Dwi Zubaidah; Arifah Hidayati; M. Noor Armi (Universitas Triatma Mulya, 2023)
This study which promotes financial literacy (X1) and fintech (X2) ascertain how financial inclusion (Z) affects the growth of MSMEs (Y). Quantitative research method employed. Primary data research data gathered directly from respondent sort of data employed study participants are all MSME players in city of Bengkulu's food industry. sample size study calculated 200 respondents using method (Hair et al., 2014) indicator 20 multiplied by 10. The smartPLS 3.0 analytic utilized to handle research data structural equation modeling (SEM) variance-based approach employed for research technique work results of study simultaneously is positive significant influence financial literacy (X1) fintech (X2) development MSMEs (Y) mediated financial inclusion (Z). the hypothesis test financial literacy variable (X1) no significant effect MSME development (Y) fintech variable (X2) significant effect MSME development (Y), financial literacy significant effect on financial inclusion (Z) fintech (X2) significant effect financial inclusion (Z), financial inclusion (Z) significant effect development MSMEs (Y) indirect effect financial literacy (X1) no significant effectdevelopment MSMEs (Y) mediated by financial inclusion (Z) fintech (X2) significant effect development of MSMEs (Y) which mediated financial inclusion (Z )